2003
DOI: 10.1055/s-2003-41256
|View full text |Cite
|
Sign up to set email alerts
|

TVT - Sonographische Beobachtungen im Hinblick auf korrekte Lage und Funktion des TVT-Bandes unter Berücksichtigung der individuellen Urethralänge

Abstract: ZusammenfassungFragestellung: Im Rahmen einer retrospektiven Studie untersuchten wir an 64 Patientinnen mittels Introitussonographie die Lage und Beweglichkeit des TVT-Bandes bei geheilten, gebesserten und bei als Therapieversager eingestuften Patientinnen. Material und Methodik: Präoperativ wurden bei allen Patientinnen zur Erfassung der Inkontinenzsymptomatik eine Anamnese, eine urodynamische Untersuchung, ein 1-Stunden-Pad-Test, ein Lebensqualitätsscore, eine gynäkologische Untersuchung mit Funktionstests u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
8

Year Published

2004
2004
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
1
10
0
8
Order By: Relevance
“…Both the localization and the configuration of the tape may be significant [24]. The ultrasound examination should be performed at rest and during the Valsalva maneuver.…”
Section: Role Of Ultrasound In Perioperative Evaluationmentioning
confidence: 99%
“…Both the localization and the configuration of the tape may be significant [24]. The ultrasound examination should be performed at rest and during the Valsalva maneuver.…”
Section: Role Of Ultrasound In Perioperative Evaluationmentioning
confidence: 99%
“…B. urethrale Bandlagen; [12,20]) erklär-lich sind und Korrekturansätze vermittelt werden. Neben der topographischen Zuordnung von Bandmaterialien konnten Kociszewski et al [11] Pressen) sich die in Ruhe unauffällig darstellende Bandtopographie im Verhältnis zur Urethra wesentlich verschieben kann und bestehende Funktionsstörungen erklärt.…”
Section: Neues Zur Diagnostikunclassified
“…A clearly positive closure pressure was demonstrable during coughing over the distal half of the functional urethral length. Determination of the topographically correct position of the TVT was carried out with the help of introital ultrasound [6]. In this ultrasound, it was shown that the Prolene tape laid correctly between the distal third and the middle third of the urethra.…”
Section: Case Reportmentioning
confidence: 99%